Verification of structural reliability of a highway bridge in the state of Rio Grande do Sul - Avila, Vinicius Heidtmann (2023)
This study deals with the evaluation of the reliability index of prestressed girders members of road bridges in relation to the ultimate limit state (ULS) of bending failure. In a wide bibliographic review of scientific works that deal with structural reliability, prestressed structural elements and road bridges, it is observed that few of these deals specifically with the reliability of girders considering the codes NBR 7188 of 2013 and NBR 7187 of 2021. A mechanical model was developed for the calculation of the beam resistant moment and the Monte Carlo Method was used to obtain a data set that represents the statistics of the structure in the ULS. To obtain the reliability index B, the first order reliability method (FORM) was used. The values obtained by the analytical method are validated using the Monte Carlo simulation method. For all evaluated cases, the value of the reliability index was higher than 4.0, which is higher than the minimum required value of 3.5, showing that the national normative recommendations for the design of beam members guarantee a very conservative level of safety.